2021
DOI: 10.1115/1.4050608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turning Angle and Turning Internal Radius on Channel Impingement Cooling for a Novel Internal Cooling Structure

Abstract: Recently, a novel internal cooling structure, namely multi-channel wall, has been put forward to enable higher overall cooling effectiveness with less coolant and pressure loss. Our previous work has proved the advantages of the design relative to conventional impingement cooling and swirl cooling. Channel impingement cooling structure, which is utilized at the turning region of the leading edge, is the critical factor to realize the high cooling performance of the design. Hence, the turning angle and turning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Analysis of articles by other authors has shown that the influence of the gas-dynamic characteristics of flows (in particular, the turbulence intensity) on the heat transfer level is of great importance in the nuclear industry when cooling nuclear reactors [5,6]. Heat transfer intensification by controlling the flow gas dynamics is widely used in the field of turbine engineering [7][8][9]. Gramespacher et al [7] investigates the effect of surface roughness on the turbulence intensity of flows and, accordingly, on the heat transfer level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of articles by other authors has shown that the influence of the gas-dynamic characteristics of flows (in particular, the turbulence intensity) on the heat transfer level is of great importance in the nuclear industry when cooling nuclear reactors [5,6]. Heat transfer intensification by controlling the flow gas dynamics is widely used in the field of turbine engineering [7][8][9]. Gramespacher et al [7] investigates the effect of surface roughness on the turbulence intensity of flows and, accordingly, on the heat transfer level.…”
Section: Introductionmentioning
confidence: 99%
“…Gramespacher et al [7] investigates the effect of surface roughness on the turbulence intensity of flows and, accordingly, on the heat transfer level. He et al [8] propose to improve heat transfer in order to increase the efficiency of cooling of turbine parts and assemblies, based on numerical simulation. The turbulence level of flows is of great importance for the heat exchange intensity in various heat exchangers [10][11][12].…”
Section: Introductionmentioning
confidence: 99%